Recovery capital, the recovery ecosystem, and substance use among recovery high school students - Jurinsky, Jordan; George, Shane S.; Riccio, Arianna A.; Finch, Andrew J.; Kelly, John F.; Hennessy, Emily A. (Frontiers in Adolescent Medicine, 2025)
IntroductionAdolescent development and substance use disorder recovery unfold within diverse contexts, where recovery capital is key to planning. This study examined the relationship between social and personal recovery capital, community recovery capital, and cannabis and alcohol use among adolescents.MethodsIn this cross–sectional study, 416 students from 20 U.S. recovery high schools reported their past 90–day alcohol and cannabis use and completed the Assessment of Recovery Capital (adapted for youth readability). Student data were merged with data from the Recovery Ecosystem Index, which measures county–level recovery ecosystem, using each high school's county as a proxy for residence. Zero–inflated Poisson regression models estimated the odds of abstinence and substance use days, with recovery capital and recovery ecosystem index as predictors, while accounting for age, race, gender, and duration of enrollment (≥90 days).ResultsThere were 378 (91%) and 360 (87%) students who provided alcohol and cannabis use data and were subsequently included in each model, respectively. Students, 47% female and 60% White person/persons/people, reported alcohol (M = 2.0; SD = 8.1) and cannabis (M = 6.0; SD = 18.0) use days, with most reporting zero days of use (284 and 266). The results indicated that the recovery capital score was positively associated with alcohol abstinence [adjusted odds ratio (aOR) = 1.03; 95% confidence interval (CI) = 1.01–1.06; P = 0.02] and cannabis abstinence (aOR = 1.03; 95% 1.01–1.06; P = 0.01). As recovery capital increased, adolescents reported fewer alcohol use days [incidence rate ratio (IRR) = 0.93, 95% CI = 0.93–0.94; P < 0.001] and fewer cannabis use days (IRR = 0.95; 95% CI = 0.95–0.96, P < 0.001). The recovery ecosystem index was not associated with alcohol or cannabis abstinence, but days of alcohol use (IRR = 1.12; 95% CI = 1.04–1.22, P = 0.01) and cannabis use (IRR = 1.10; 95% CI = 1.05–1.15; P < 0.001) increased as the index increased.DiscussionFindings suggest that greater recovery capital is linked to greater alcohol and cannabis abstinence among recovery high school students. Unexpected was that a higher recovery ecosystem index score was associated with more substance use days. Youth–focused recovery supports could benefit from examining how changes in individual recovery capital influence service usage and how service usage, in turn, impacts recovery capital. There is also the need for a youth–tailored recovery ecosystem measure which focuses on factors unique to their developmental phase.